ROOFTOP THEMED CULINARY TOURISM DEVELOPMENT STRATEGY IN INDONESIA - Vivaldy Ismail; Muhammad Xavier Saputra (Sekolah Tinggi Pariwisata Mataram, 2022)
Indonesia is a tourism place that is very famous for culinary tourism. Culinary businesses such as restaurants and bars that are very popular today are not only spoiling the tongue, but also spoiling the eyes. Therefore, the Rooftop part of the building is not allowed to be used by the public, but this is a very good opportunity if it can be used properly it will become a new tourist destination that will be popular especially for Millennial Tourists. This phenomenon does not only occur in Indonesia, but also becomes a trend of urban tourism in the world. The analytical method used in this paper is a qualitative descriptive method of observing tourist attractions with the theme of the rooftop restaurant and bar. This study found that rooftop-based culinary tourism objects have a SWOT analysis theory as follows: 1. Strengths, 2. Weaknesses, 3. Opportunities, 4). Threats (threats).